The role of job satisfaction in the person-organization fit relationship in terms of goal pursuit strategies, and mental health - Marta Roczniewska; Sylwiusz Retowski (Nofer Institute of Occupational Medicine, 2014)
Background: Person-organization (P-O) fit is a predictor of job satisfaction, and a misfit is a potential stressor. We aimed to examine the consequences of fit between a person and an organization in terms of goal-pursuit strategies. We tested whether job satisfaction mediates the relationship between regulatory fit and mental health. Material and Methods: Research was conducted in a group of 169 employees. They were asked to fill in questionnaires assessing their chronic work regulatory focus, organizational regulatory focus and job satisfaction. To measure mental well-being we administered the General Health Questionnaire (GHQ-28). We conducted mediation analysis in regression. Results: The results of the mediation analysis confirmed the mediating role of job satisfaction in the relation between regulatory focus misfit and physical and mental symptoms of distress. Conclusions: The results of this study point to the fact that P-O fit can relate to goal pursuit strategies. It influences not only job satisfaction, but also employees' health. The conclusions can be applied in the human resources management practices, e.g., it may serve as a useful argument to motivate employers to shape goals and strategies individually by managers, according to employees' preferences. The results should be interpreted with caution because of non-random sampling. Med Pr 2014;65(5):621-631